PERANCANGAN SISTEM KEAMANAN TEMPAT PENYIMPANAN BARANG MENGGUNAKAN KONSEP LASER LIGHT SEBAGAI ALARM DAN NOTIFIKASI BERBASIS IoT - Dito Juliansyah, Dito; Sulaiman, Sulaiman; Ariandi, Muhammad; Dasmen, Rahmat Novrianda (Fakultas Teknik Universitas Muhammadiyah Sumatera Barat, 2025)
This study aims to evaluate the performance of various sensors and security systems based on environmental changes and access conditions. Power supply measurements show stability with an average voltage of 24.094 V and an error rate of 0.43%, which is within the 5% tolerance limit. The LDR sensor proved effective in detecting light changes with consistent resistance values in bright, dim, and dark conditions. The door sensor demonstrated reliability in responding to door condition changes with an average response time of 50 milliseconds. The RFID system efficiently processes registered and unregistered cards quickly, ensuring only authorized access. Overall, the security system is assessed to respond swiftly to potential threats, providing adequate protection.Keywords: Power supply, LDR sensor, Door sensor, RFID, Security system, Quick response